DIFUSI ISLAM MELALUI MEDIA CETAK - Halwati, Umi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2012)
Diffussion of Islam through printed media (da’wah bi al-qalam, bi al-kitabah) is anintegrated part of the study of Islamic preaching (da’wah). It is one of da’wah media or channels.One of the main criteria of da’wah media is its effectiveness and efficiency.Printed media is an alternative of da’wah media that is effective and efficient enough. Thediffussion of Islam through printed media can be found in the form of articles, features, and bookreviews. The texts in mass media represent the various kinds of da’wah which are developingrecently.